(untitled) (Revista de Medicina Clinica, 2023)
Clinical Snapshot on "Endoscopic Imaging After Recanalization of the Right Main Bronchus through Bronchoscope with Stent Placement" presented in volume 7 issue 1 of 2023 of Revista de Medicina Clínica.